Pengaruh Debt Covenant dan Financial Distress Terhadap Konservatisme Akuntansi : Studi Empiris pada Perusahaan Consumer Noncyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2022 - Ayu Anix Matunisa; Wulandari Cahyani Putri (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The purpose of this research is to analyze of Debt Covenant and Financial Distress on accounting conservatism in Companies of Consumer non cyclicals listed on the Indonesian Stock Echange for the 2021-2022 period. Sampling in this research used purposive sampling technique and abtaained 52 samples of companies. The data analysis method used is quantitative data analysis using panel data regression analysis and using Eviews 12 computer program tools. The result of this research partially show that the Debt Covenant have an effect on accounting conservatism and Financial Distress has no effect on accounting conservatism. Meanwhile simultaneously, Debt Covenant and Financial Distress have an effect on accounting conservatism reaction with R2 contribution of 12%.